A MoS2-templated oxidation-etching strategy to synthesize hollow δ-MnO2 nanospheres as a high-performance electrode for supercapacitor. Issue 14 (1st October 2018) - Chai, Chaojing; Liu, Aifeng; Wang, Yao; Lu, Yanpeng; Che, Hongwei
Abstract: Hollow δ-MnO2 nanospheres have been synthesized through an in situ redox etching reaction using MoS2 nanospheres as a sacrificial template in a KMnO4 aqueous solution. The formation mechanism for hollow δ-MnO2 nanospheres was investigated through designing the time-dependent experiments on the hydrothermal redox etching reaction. Based on the advantages of hollow structure, hollow δ-MnO2 nanospheres as an electrode for supercapacitors demonstrated a high specific capacitance of 394 F g −1 at 1 A g −1 and good cycle stability with 95.2% capacitance retention after 5000 cycles at 5 A g −1 . Furthermore, an asymmetric supercapacitor device was assembled using hollow δ-MnO2 nanospheres as the positive electrode, which delivered an energy density of 24.4 W h kg −1 at a power density of 999 W kg −1 . These findings suggest a great promise for hollow δ-MnO2 nanospheres in high-performance supercapacitors. Graphical abstract: Hollow δ-MnO2 nanospheres have been successfully synthesized using a MoS2 -templated in-situ redox etching strategy, which demonstrate a high specific capacitance as an electrode for supercapacitors. fx1